Latitudinal and MLT dependence of the seasonal variation of geomagnetic field around auroral zone. Issue 3 (1st August 2017) - Zhu, Jin; Du, Aimin; Ou, Jiaming; Xu, Wenyao
Abstract: Seasonal variation of geomagnetic field around auroral zone is analyzed in terms of geomagnetic latitude, magnetic local time (MLT) and geomagnetic condition in this study. The study uses horizontal component (H) of geomagnetic field obtained from 6 observatories located in geomagnetic latitude of 57.8°N–73.8°N along 115°E longitudinal line. The results indicate that seasonal variations of geomagnetic field around auroral zone are different combinations of annual and semiannual variations at different latitudinal ranges. Both annual and semiannual variations show distinct MLT dependency: (1) At dayside auroral latitudes (around 72°N geomagnetic latitude), geomagnetic field shows distinct annual variation under both quiet and disturbed conditions. Furthermore, the annual component is mainly contributed by data of dusk sector. (2) At nightside auroral latitudes (around 65°N), geomagnetic field shows semiannual dominated seasonal variation. Under quiet conditions the annual component is comparable to the semiannual component, while under disturbed conditions, the semiannual component is twice as much as the annual component. Under quiet conditions, the semiannual component is mainly contributed by 1300–1400 MLT, while the annual component has two peaks: one is around 1100–1300 MLT and the other is around 2000–2200 MLT. Under disturbed conditions, the semiannual component is mainly contributed by data around midnight, while the annual component is mainly contributed by dusk sector. (3) At subauroral latitudes (around 60°N), annual variation is comparable to semiannual variation under both quiet and disturbed conditions. Both annual and semiannual components show similar MLT dependencies as that of nightside auroral latitudes.